Percepción y conocimiento popular sobre el cocodrilo Crocodylus acutus (Reptilia: Crocodylidae) en zonas aledañas al río Tempisque, Guanacaste, Costa Rica - Valdelomar, Valerie (2012)
Perception and popular culture about the crocodile (Crocodylus acutus) near Tempisque River, Guanacaste, Costa Rica. The American crocodile (Crocodylus acutus) is an endangered species due to habitat loss and illegal hunting. Its population has recovered significantly in the Tempisque River, Costa Rica; nevertheless, they are still vulnerable because their niche and habitat overlap human activities, which causes a human-crocodile conflict worsened by mistaken popular beliefs. We evaluated popular perception and knowledge with 336 surveys in 11 towns of Carrillo, Santa Cruz and Cañas, in Guanacaste. We also tested the relationships among residence, occupation, sex, age and educational grade and perception of danger. The inhabitants believe there is an excess of crocodiles near their towns, and the reptiles are considered dangerous and aggressive. Overall, they know little about the biology of C. acutus, but much about its behavior, conservation status and state protection. To regulate the crocodile population, they consider elimination or relocation necessary (both have different implications). They seem, however, willing to cooperate in management plans. It is important to choose key towns to strengthen existent environmental education programs with contents about the biology of the species, security, and conflict avoidance. In the near future, we recommend the establishment of a management plan to regulate crocodile population in some specific spots within the Tempisque River’s Basin.